2017
DOI: 10.1186/s40066-016-0080-6
|View full text |Cite
|
Sign up to set email alerts
|

Household food insecurity and associated factors in West Abaya district, Southern Ethiopia, 2015

Abstract: Background: Subsistence farming in West Abaya district is sited in an area prone to drought. Thus, poor food security is a principal concern. But, this has been less documented. Therefore, this study aimed to determine the magnitude of household food insecurity and identify associated factors in West Abaya district, Southern Ethiopia, 2015.Methods: Community-based cross-sectional study was done on 779 households from February to March, 2015. Out of 24 kebeles (lowest administrative units) in the district, 9 ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
23
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 17 publications
11
23
2
Order By: Relevance
“…Thus, lower household food insecurity in this study might be associated with harvesting season of the year where the study was performed. In contrary, the finding observed in this study tends to be higher than the findings of some studies such as Pakistan (19%), Humbo (28.4%) and urban areas of Ethiopia (28.0%) [10,[27][28][29]. The disparity might be due to the agroecological differences in settings and socioeconomic variations among study areas.…”
Section: Discussioncontrasting
confidence: 56%
“…Thus, lower household food insecurity in this study might be associated with harvesting season of the year where the study was performed. In contrary, the finding observed in this study tends to be higher than the findings of some studies such as Pakistan (19%), Humbo (28.4%) and urban areas of Ethiopia (28.0%) [10,[27][28][29]. The disparity might be due to the agroecological differences in settings and socioeconomic variations among study areas.…”
Section: Discussioncontrasting
confidence: 56%
“…Available literature suggests that about 60% of rural households of Bangladesh have been suffering from food insecurity [21]. In the present study, we found that food insecurity was negatively associated with family size and similar findings were reported in other studies [22,23]. Household food insecurity was also associated with educational status, with similar findings in three other studies [22,24,25].…”
Section: Discussionsupporting
confidence: 90%
“…Then again the burden of rural household food insecurity was identified as 38% and 9% of households were severely food insecure in the rural setting. Female headed household, larger family size, households head aged > 65 years, having lesser farm land and single household head had negative effect on rural household food insecurity [9]. …”
Section: Main Textmentioning
confidence: 99%
“…Among the subjects examined by the investigator; bacterial loads of dairy cow milk, household food insecurity and the state of family planning practices were a few to cite [2, 6, 9, 11]. Ahead of shown subjects; determinants of infant and young child feeding (IYCF) practices, occurrence of SAM in under five children and treatment procedures, treatment outcomes of SAM and its predictors were also areas investigated by the researcher [3–5, 7, 8, 10].…”
Section: Introductionmentioning
confidence: 99%